Hubungan Lama Kontak dengan Dermatitis Kontak Akibat Kerja pada Karyawan Pencucian Mobil di Denpasar Utara - I Gusti Ayu Pratiwi Utami Asbita; Made Sudarjana; Anak Agung Sri Agung Aryastuti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Occupational contact dermatitis is an inflammatory skin condition that shows clinical abnormalities in the form of erythema, vesicles, and pruritus caused by contact with materials in the workplace. One of the factors thought to influence the occurrence of contact dermatitis is the duration of contact. The longer the contact with chemicals, the more damage the skin cells located in the deeper layers and the occurrence of damage to skin function, making it easier for dermatitis to occur. This study aims to determine the relationship between the duration of contact of vehicle washing workers with occupational contact dermatitis in car wash employees in North Denpasar sub-district. The research data were obtained from the Nordic Occupational Skin Questionnaire (NOSQ) and Mathias questionnaires involving 30 vehicle wash workers in North Denpasar sub-district. Data were analyzed by SPSS program using chi-square test. The results showed that the majority of vehicle washing workers who work in North Denpasar are aged 16-25 years (86.7%), the majority of workers have a contact duration of less than 7 hours (53.3%), and the majority of workers experience occupational contact dermatitis (63, 3%). The results of the analysis showed that there was a relationship between duration of contact and the incidence of occupational contact dermatitis in car wash employees in North Denpasar District (p = 0.017). The conclusion that can be drawn is there is a relationship between duration of contact with the incidence of occupational contact dermatitis in car wash employees in North Denpasar District.